Assessment of Three Fish Species Stock for Conservation and Management Policy in River Imo, Nigeria - C., Ogueri; G.S., Adaka; C., Utah; H.C, Madu; C.B., Ekeledo; C.F., Ezeafulukwe; A.J., Bunu; D.C., Njoku; U.K., Chinnah; U.E, Cyril (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The rates of Growth, recruitment, mortality, and exploitation of three important fish species of the River Imo, Nigeria, were investigated, aimed at providing information on their conservation status and management policies for their sustainability. These species are big-sized and fleshy, and they are Gymnarchus niloticus (Cuvier 1829), Clarias gariepinus (Burchell 1822) and Distichodus notratus (Gunther 1864). Assorted fishing gears were used to catch the species fortnightly from January to July 2023, and data on their standard length were taken to the nearest centimeter (cm). 503,129 specimens were examined and measurements analyzed with the Electronic Length Frequency Analysis (ELEFAN II) fitted into the von Bertalanffy Growth Model (VBGM) of L(t) = L∞ [1 – e –k(t-t0)] with FAOICLARM (FISAT) tools software. Asymptotic length (L∞) for G. niloticus = 210cm, C. gariepinus = 94.50 cm and D. rostratus = 68.25cm. Comparing the stock parameters of total mortality (Z), Fishing Mortality (F), Exploitation rate (E) and length of sexual maturity (Lm), G. niloticus was observed to be over-exploited (E = 0.84), D. rostratus was near optimal level of exploitation (E = 0.51) while C. gariepinus was not over- exploited (E = 0.24). Recommended management policies are restriction on the use of small mesh sizes (≤ 3 cm); prohibition of the catches of sexually immature individuals (for G. niloticus sizes ≤ 140.0 cm, C. gariepinus ≤ 63.0cm and D. rostratus ≤ 45.5 cm) and enforcement of closed fishing season on the observed peak of recruitment: April – May – June – July in River Imo.